Nanomaterials in drug delivery, imaging, and tissue engineering - Tiwari, Ashutosh, 1945-; Tiwari, Atul.; ebrary, Inc. (Hoboken, N.J. : John Wiley & Sons, 2013)
"Nanoscopic therapeutic systems incorporate therapeutic agents, molecular targeting and diagnostic imaging capabilities and are emerging as the next generation of multifarious nanomedicine to improve the therapeutic outcome including chemo and translational therapy. This reference work is one of the first to cover Nanotheragnostics which is the new edge of nanomedicine combining both diagnostic and therapeutic elements at nano level.This large multidisciplinary reference work is has four main parts: Biocompatible Nanomaterials; Nanomedicine: Drug Gene and Cell Delivery; Multi-functional Nanocarrier: Diagnosis, Imaging and Treatment; Tissue Engineering/Regenerative Medicine"--
pt. I. Biomedical nanomaterials -- pt. II. Advanced nanomedicine -- pt. III. Nanotheragnostics -- pt. IV. Nanoscaffolds technology.
Includes bibliographical references and index.
Electronic reproduction.
Keywords: Biomedical materials; Drug delivery systems; Tissue engineering; Electronic books